PENGARUH KOMUNIKASI INTERPERSONAL TERHADAP PELAYANAN PRIMA MELALUI MOTIVASI KERJA DI KANTOR SATUAN POLISI PAMONG PRAJA KABUPATEN PAK PAK BHARAT - Marslam Ganda Pandapotan Limbong; Heri Arman Nduru (LPPM Universitas Cipta Mandiri, 2024)
This study discusses the influence of interpersonal communication on excellent service through work motivation at the Pak Bharat District Civil Service Police Unit Office, namely the purpose of this study is to determine the influence of interpersonal communication on excellent service at the Pak Bharat District Civil Service Police Unit Office and to find out how much influence interpersonal communication has on excellent service through work motivation at the Civil Service Police Unit Office District Mr. Pak Bharat. The population in this study consisted of 40 samples taken randomly and the method used in this study was quantitative method, where this research was carried out at the office of the Civil Service Police Unit of Pak Pak Bharat District. To find out the results of this research using SPSS 25 contained in the significant test t or with the r test where in the t test there is a significant influence of interpersonal communication on excellent service through work motivation which is explained by the test results if obtained t count 3.639> t table 2.0243 contained in interpersonal communication and t count 11.331> From t table 2.0243 contained in work motivation, this result shows that there is a positive and significant influence.